1995
DOI: 10.1002/jbmr.5650100509
|View full text |Cite
|
Sign up to set email alerts
|

Surface-associated proteins from Staphylococcus aureus demonstrate potent bone resorbing activity

Abstract: Staphylococcus aureus infections are associated with rapid bone destruction in conditions such as osteomyelitis, bacterial arthritis, and infected orthopedic implant failure. How this bacterium induces bone destruction has not been defined. In studies of the role of oral Gram-negative bacteria in periodontal pathology, we have established that cell surface-associated proteins (SAPs) are potent stimulators of bone resorption. The surface-associated components from S. aureus have now been isolated and demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…Bacterially induced osteoclastogenesis is not without precedent (see review by Nair et al, 1996). Multinucleation and TRAP production by spleen cells has been reported following treatment with Porphyromonas gingivalis, a periodontal pathogen, or lipopolysaccharide from E. coli (Abu-Amer et al, 1997;Jiang et al, 2002), and the addition of surface-associated material from P. gingivalis, Actinobacillus actinomycetemcomitans, or Staphylococcus aureus to bone marrow cultures reportedly causes multinucleation and bone resorption in vitro (Wilson et al, 1986;Wilson et al, 1993;Nair et al, 1995), although this effect may be due to an increase in RANKL by associated osteoblasts, rather than a direct effect on osteoclast precursors. However, incubation periods of 10 days or more were routine in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterially induced osteoclastogenesis is not without precedent (see review by Nair et al, 1996). Multinucleation and TRAP production by spleen cells has been reported following treatment with Porphyromonas gingivalis, a periodontal pathogen, or lipopolysaccharide from E. coli (Abu-Amer et al, 1997;Jiang et al, 2002), and the addition of surface-associated material from P. gingivalis, Actinobacillus actinomycetemcomitans, or Staphylococcus aureus to bone marrow cultures reportedly causes multinucleation and bone resorption in vitro (Wilson et al, 1986;Wilson et al, 1993;Nair et al, 1995), although this effect may be due to an increase in RANKL by associated osteoblasts, rather than a direct effect on osteoclast precursors. However, incubation periods of 10 days or more were routine in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralisation of TNFα and IL-6 fully abolishes SAM-stimulated osteoclastogenesis, with antagonism of IL-1 having only a partial effect (Meghji et al, 1998; Nair et al, 1995). The effect of this SAM on osteoclast formation and stimulation of resorption does not require co-culture with osteoblasts, and does not require RANKL signalling (Lau et al, 2006).…”
Section: Inflammation In Bone Infectionmentioning
confidence: 99%
“…Work in our own laboratory has shown that S. aureus and S. epidermidis produce surface-associated proteins that can stimulate bone breakdown in an in vitro assay (Meghji et al, 1997; Nair et al, 1995). These surface-associated proteins and capsular material appear to promote the formation and activation of the bone-resorbing osteoclast (Lau et al, 2006; Meghji et al, 1998).…”
Section: Staphylococcal Virulence Determinantsmentioning
confidence: 99%
“…As such, any interference with these integrated cell types can result in abnormal bone remodeling. Bacteria such as S. aureus and their products can be potent stimulators of resorptive bone loss (Nair et al, 1995, 1996). While bacteria can directly damage bone by producing acids and proteases, they can also stimulate osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 99%